Manajemen Penghimpunan dan Penyaluran Dana Zakat Infak Sedekah di Lazismu Kabupaten Gresik - Muhammad Farid Rusdhianto; Iwan Setiadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Zakat is one of the pillars of Islamic economics as one of the Pillars of Islam which is mandatory for those who meet the requirements, Zakat is an effort to equalize income. The aim of this research is to analyze the management of the ZIS Fund, analyze the accountability and transparency of the financial reports of the LAZISMU institution, and analyze the management capabilities using digital technology. The research object is the LAZISMU Muhammadiyah Gresik Regional Leadership. This research uses a qualitative descriptive design, where the data source is primary data which is collected by means of interviews and documentation. Qualitative descriptive data analysis is an approach used to understand and interpret non-numerical data through explaining, describing and classifying phenomena. The research results are proven. Firstly, Fund Collection Management has been successful in collecting ZIS funds from the community in accordance with the targets set. Management and Distribution Where the collected funds are managed and distributed appropriately, in accordance with the principles of ZIS fund management to help those in need. Both Zakat, Infaq and Alms Institutions (ZIS) have prepared financial reports in accordance with ZIS accounting standards. Financial reports allow institutions to assess their performance in collecting and distributing ZIS funds. This helps in taking strategic decisions to increase the effectiveness of ZIS-funded programs. ZIS financial reports ensure that all funds received and disbursed by the institution are clearly recorded and can be checked. This is important to maintain the trust of donors and the public who entrust their funds to the Institution. Third, managing Zakat, Infaq and Alms (ZIS) funds using digital technology has a number of advantages that can increase effectiveness, efficiency and transparency in managing these funds. Below are some of the main benefits of using digital technology in ZIS fund management. Ease of Fund Collection where with digital technology, such as online payment applications, donors can make donations quickly and easily via cellphone or computer. This makes it easier for people to access ZIS activities, anytime and anywhere